Titanium alkalinization improves response of osteoblasts to zoledronic acid - Real, Rodrigo Paes Vila; Pansani, Taisa Nogueira [UNESP]; Cardoso, Lais Medeiros [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Basso, Fernanda Gonçalves (American Vacuum Society, 2022)
This investigation is aimed to determine the effect of the modification of titanium surface with NaOH on the metabolism of osteoblasts treated with zoledronic acid (ZA). Machined and NaOH-Treated titanium disks were used. Surfaces were characterized by scanning electron microscopy, confocal microscopy, and x-ray photoelectron spectroscopy (XPS) analysis. Human osteoblasts were seeded onto the disks. After 24 h, cells were treated with ZA at 5 μM for 7 days. At this point, cell viability, collagen synthesis, total protein production, alkaline phosphatase activity, and mineral nodule deposition were assessed. The results of surface roughness were descriptively and statistically analyzed (t-Student), while the XPS results were qualitatively described. Cell metabolism data were analyzed by the analysis of variance two-way and Tukey tests at a 5% significance level. The results demonstrated that NaOH-Treatment increased surface roughness (p <.05) and confirmed the presence of sodium titanate and a pH switch on the NaOH-Treated disks. This modification also resulted in higher cell viability, collagen synthesis, total protein production, and alkaline phosphatase by osteoblasts when compared to cells seeded onto machined disks (p < 0.05). In the presence of ZA, all cellular metabolism and differentiation parameters were significantly reduced for cells seeded on both surfaces (p < 0.05); however, the cells seeded onto modified surfaces showed higher values for these parameters, except for mineral nodule deposition (p < 0.05). NaOH modification improved cell adhesion and metabolism of osteogenic cells even in the presence of ZA. The surface modification of titanium with NaOH solution may be an interesting strategy to improve metabolism and differentiation of osteoblasts and accelerate osseointegration process, mainly for tissues exposed to ZA.